Travessias de formação e atuação docente: movimentações identitárias presentes nas práticas discursivas de professores de licenciaturas da UFPA - SILVA, Gerlândia de Castro (Universidade Federal do Pará, 2011)
This dissertation discusses the varying professional roles assumed by a teacher at the Federal University of Para (UFPA). As source material for this work, their life stories, based upon oral narratives were used. The research focuses on the discovery about what are the different roles assumed by those teachers during their entire professional life as a teacher. The main question studied was: what are the most important roles assumed by such a teacher and how they are related among themselves? The theoretical and methodological approach used was based upon Foucault's and Larrosse's seminal works. These thinkers suggest that oral speeches about one's own life story carry strong significances and can be given important meanings and interpretations. As results, the study of these oral narratives showed us that the university teachers at UFPA assume many and varied roles during their professional life at the institution and that at each time they are questioned about those different roles. Besides, they are forced sometimes to assume certain behaviors accepted by the establishment. We conclude for the necessity of remaking, reconstructing other roles for those teachers involved with the power/knowledge institutions game.